The Effect Of Information Gap Activity On The Interactional Competence Of Tenth-Grade Students at SMAN 1 Tanjungpinang - Dinda Pritaputri Ramadhan; Satria Agust; Elsa Ernawati Nainggolan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Interactional competence is an important aspect of English speaking instruction because students need to respond, manage turn-taking, repair communication breakdowns, and maintain shared meaning with interlocutors. This study aimed to examine the effect of Information Gap Activity on the interactional competence of tenth-grade students at SMAN 1 Tanjungpinang. The study employed a quantitative pre-experimental approach with a one-group pre-test and post-test design. The participants were 36 students of class X-16 in the 2025/2026 academic year. Data were collected through paired speaking tests assessed by two raters using five indicators: responsiveness, turn-taking, repair, fluency, and accuracy. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon signed-rank test. The findings showed that the mean score increased from 57.44 in the pre-test to 75.94 in the post-test, with all students improving. The Wilcoxon test showed a significant difference (Z = -5.261; p < .001). This implies that Information Gap Activity effectively promotes interactive, collaborative, and meaning-oriented speaking instruction.